Antecedent and consequences of consumers' satisfaction in online grocery shopping. (17th December 2021) - Kusuma, Adinda Citra; Najib, Mukhamad; Hermadi, Irman
The rapid development of the internet and changes in consumption patterns in Indonesia encourage consumers to shop for various products online including shopping for daily necessities such as groceries. This study aims to analyse the effect of online grocery shopping experience factors on satisfaction and the effect of consumer satisfaction on trust and loyalty. Data collection was carried out utilising online survey of 169 respondents who had shopped online for groceries. The data were analysed using the structural equation modelling (SEM) method using SmartPLS software. The analysis shows that the online shopping experience has a significant and positive influence on consumer satisfaction except variable customisation and ease of return. Furthermore, consumer satisfaction has a significant and positive effect on trust and loyalty. The experience of consumers in shopping online can be used as a reference to increase satisfaction so that consumers become trustworthy and loyal.